If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y = -0.62x Solving y = -0.62x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Simplifying y = -0.62x
| 5x^3-14x^2-6x=0 | | 9z+12=13+18z | | 12+10x=14x+5 | | 5(a+20)=25 | | -x+(-x+45)=25 | | -5x=7-4x+8 | | -2p^2+70p=0 | | 4(2x+3)=7x+15 | | 24b+3a=0 | | -q-11=2q+14 | | 8a+11=7+15a | | 3a+24b=0 | | 3+12y=6+18y | | -x+(-x+45)=20 | | 9a+7=2+12a | | 10b+8=15b+4 | | 2(3x+4)=5+1 | | 4a-18b=0 | | 6y-9=7y-1 | | 3-x=2.25 | | 6x^2+24x+30=0 | | 2(3X+5)=5X+5 | | 7z+11=0 | | 132=2l+3w | | 10=3z-8 | | 3x-(6-x)=18 | | 5d-2=2d+6 | | 36x=36+121+1 | | t^2-5t+2fort=-4 | | -x=-0.12 | | f(0)=-2x | | 9+11x=107+x |